Association of Polymorphisms in Pharmacogenetic Candidate Genes with Propofol Susceptibility - Zhong, Qi (Sci Rep, 2017)
Significant individual susceptibility to intravenous anesthetic propofol exists. The etiology of individual variability in the response to propofol may be influenced by genetic polymorphisms in metabolic and functional pathways. With current pharmacogenetics and modern molecular biology technologies, it is possible to study the influence of genetic polymorphisms on susceptibility to propofol. When inducing general anesthesia with intravenous propofol, high individual susceptibility to propofol was found. Using Sequenom MassARRAY single-nucleotide polymorphism (SNP) genotyping, we identified a mutation (rs6313) in the 5HT2A gene that was correlated to individual susceptibility to propofol effect-site concentration (Cep) and onset time of propofol induction. Carriers of the minor allele (G) of 5HT2A rs6313 required less propofol (20% decrease in Cep) and less time (40% decrease in onset time) to induce anesthesia. Moreover, associations were found between the gamma-aminobutyric acid (GABA) receptor SNP rs2279020 and the SCN9A SNP rs6746030 and the susceptibility of bispectral index (BIS) after propofol-induced anesthesia. In addition, dominant mutations in GABAA1 rs2279020, GABAA2 rs11503014, and CHRM2 rs1824024 were putatively associated with cardiovascular susceptibility to propofol anesthesia. No gene-gene interactions were found through a standardized measure of linkage disequilibrium and a multifactor dimensionality reduction analysis. Our results suggest that genetic polymorphisms related to mechanisms of propofol anesthesia are involved in propofol susceptibility.